405 nm ultraviolet photodetector based on tungsten disulphide thin film grown by drop casting method. Issue 18 (24th October 2019) - Ahmad, Harith; Rashid, Haroon
ABSTRACT: In this work, a tungsten disulphide or WS2 based heterojunction photodetector device is fabricated on top of Si substrate by simple drop casting. Raman shifts are observed at 350.16 and 419.36 cm −1, confirming the successful growth of the WS2 and the non-stoichiometric WS2 layers which are verified by energy-dispersive X-ray (EDX) spectroscopy. The device is characterized for its optoelectronic properties in the ultraviolet (UV) range of 405 nm. Current–voltage ( I–V ) measurement is performed to obtain the I–V curves of the photodiode under laser illumination at 30.219, 56.335, 80.457, 106.998 and 129.28 mW.cm −2 . The photocurrent is found to be highly dependent on the laser power. The fabricated device has a high responsivity of 145.52 mA/W and a high detectivity of 1.248 × 10 11 Jones for an incident laser power density of 129.28 mW.cm −2 . These observed results are promising and indicate the viability of the proposed design for optoelectronic applications.